The role of the Banque de l’Agriculture et du Développement Rural (BADR) in reducing poverty through the “Companion Loan” facility: A case study of a sample of BADR Bank Customers — Case of the Guelma Agency - Adil, Allel (The International tax journal, 2026)
This study examines the role of the ‘Al-Qard al-Rafiq’ facility in meeting the financial needs of customers of the Guelma agency of the Banque de l’Agriculture et du Développement Rural (BADR), and assesses customer satisfaction with the facility. The study also seeks to identify the role this programme plays in creating employment opportunities and contributing to poverty reduction. The dimensions of this facility were operationalised as follows: The first: Access to the loan, including usage/transactions, legal procedures, difficulties encountered and file preparation. The second: dimension is related to financing, including solving financing-related problems, developing business activity and bank monitoring, among others. The third: dimension is related to repayment and includes the specified repayment period, repayment conditions and difficulties customers faced during repayment. The fourth: dimension is related to loan development in Algeria, including whether it is considered the most important means for farmers, whether it helps to develop production and whether it meets all financial needs. The study targeted the BADR bank in Guelma. A questionnaire was used as the data collection tool. It was administered to a sample of 70 customers.